2009
DOI: 10.1080/08927010802444275
|View full text |Cite
|
Sign up to set email alerts
|

The potential of nano-structured silicon oxide type coatings deposited by PACVD for control of aquatic biofouling

Abstract: SiO(x)-like coatings were deposited on glass slides from a hexamethylsiloxane precursor by plasma-assisted CVD (PACVD). Surface energies (23.1-45.7 mJ m(-1)) were correlated with the degree of surface oxidation and hydrocarbon contents. Tapping mode AFM revealed a range of surface topologies with Ra values 1.55-3.16 nm and RMS roughness 1.96-4.11 nm. Settlement of spores of the green alga Ulva was significantly less, and detachment under shear significantly more on the lowest surface energy coatings. Removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 34 publications
7
33
1
Order By: Relevance
“…In this case, bacterial attachment decreases with increasing CQ ratio or bacterial removal increases with increasing CQ ratio. This explains the experimental results by Akesso et al (2009b), ie the number of adhered dehydrated P. fluorescens decreased, or removal rate increased, with increasing CQ ratio. .…”
Section: Discussionsupporting
confidence: 71%
“…In this case, bacterial attachment decreases with increasing CQ ratio or bacterial removal increases with increasing CQ ratio. This explains the experimental results by Akesso et al (2009b), ie the number of adhered dehydrated P. fluorescens decreased, or removal rate increased, with increasing CQ ratio. .…”
Section: Discussionsupporting
confidence: 71%
“…An opposite effect was observed in our experiments. Concerning the attachment of Marinobacter hydrocarbonoclasticus, it was observed to increase with increasing the water contact angle of the silicon oxide surfaces [41], being in good agreement with our observations. The mechanism of bacteria adhesion is very complex, depending not only on the surface physicochemical properties but also on the properties of the bacteria.…”
Section: Marine Bacteria: Attachment and Adhesion Strengthsupporting
confidence: 81%
“…However this correlation does not apply in the case of the present study as lower bacteria attachment was observed for the plasma treated (harder) surface. Recent bacteria studies using silicon oxide coatings deposited by plasma-assisted chemical vapour deposition (PACVD) methods showed that the attachment of Pseudomonas fluorescens decreased with increasing the surface water contact angle, the same trend being observed for Cobetia marina [41]. An opposite effect was observed in our experiments.…”
Section: Marine Bacteria: Attachment and Adhesion Strengthsupporting
confidence: 55%
See 1 more Smart Citation
“…13,[25][26][27][28][29][30] In the development of marine coatings, there are a variety of approaches used, which most commonly involve (a) incubating a monoculture of bacteria with a coated surface to allow cell attachment, Another recently developed high-throughput assay involves measuring the retention and then retraction of a developed biofilm on a coating surface. 28 The technique involves incubating coated multiwell plates with bacterial suspensions to allow biofilms to develop.…”
Section: Assays Of Bacterial Adhesionmentioning
confidence: 99%